The Experience of the Inter-American Human Rights System - González, Felipe (Victoria University of Wellington Law Review, 2009)
This article is one of four which provide a useful comparative paradigm to any discussion of a Pacific human rights charter or regional mechanism. The article describes the Inter-American system of human rights protection, which stretches across the Americas. After an historical introduction, the article analyses the advances that took place after 1990. The discussion focuses mainly on the roles of the Inter-American Commission on Human Rights and the Inter-American Court of Human Rights. The article concludes that the system is able to influence state behaviour and has made significant contributions to the protection of human rights in the region.